LITERARY TOPOGRAPHY OF THE BORDERLAND. THE CASE OF SLAVONIA - Dyras, Magdalena (Porównania, 2017)
The regionalist spirit has been revived during recent years in Croatia. The spirit can be called “new regionalism” as opposed to the tendencies which shaped the Croatian culture for centuries. The new situation can also be referred to as “map decentralization” which is visible in the interest in fringe areas and peripheries. Slavonia, the area of intersection and meeting of different cultures, is also undergoing significant changes. In the Croatian prose there are attempts at recreating the Central European spirit of the region by means of finding traces of the past due to a kind of literary archeology which aims at finding what Aleida Assmann would call “traces, relicts, furrows and wounds” which characterize the particular places. An interesting case of such searching is the prose of authors of German origin, particularly Ludwig Bauer who is the author of a novel which revives the spirit of the borderland.